Guanitrypmycin Biosynthetic Pathways Imply Cytochrome P450 Mediated Regio‐ and Stereospecific Guaninyl‐Transfer Reactions - Liu, Jing; Xie, Xiulan; Li, Shu‐Ming (Angewandte Chemie International Edition, 2019)
Mining microbial genomes including those of Streptomyces reveals the presence of a large number of biosynthetic gene clusters. Unraveling this genetic potential has proved to be a useful approach for novel compound discovery. Here, we report the heterologous expression of two similar P450‐associated cyclodipeptide synthase‐containing gene clusters in Streptomyces coelicolor and identification of eight rare and novel natural products, the C3‐guaninyl indole alkaloids guanitrypmycins. Expression of different gene combinations proved that the cyclodipeptide synthases assemble cyclo‐l‐Trp‐l‐Phe and cyclo‐l‐Trp‐l‐Tyr, which are consecutively and regiospecifically modified by cyclodipeptide oxidases, cytochrome P450 enzymes, and N‐methyltransferases. In vivo and in vitro results proved that the P450 enzymes function as key biocatalysts and catalyze the regio‐ and stereospecific 3α‐guaninylation at the indole ring of the tryptophanyl moiety. Isotope‐exchange experiments provided evidence for the non‐enzymatic epimerization of the biosynthetic pathway products via keto–enol tautomerism. This post‐pathway modification during cultivation further increases the structural diversity of guanitrypmycins. Novel pyrroloindoline alkaloids: Eight rare natural products were identified and their biosynthetic pathways were elucidated by heterologous expression of two gene clusters. Cytochrome P450s as key enzymes catalyze the regio‐ and stereospecific transfer of a guaninyl moiety to C3 of the indole ring in cyclo‐l‐Trp‐l‐Phe (Tyr). Non‐enzymatic epimerization via keto–enol tautomerism further increases structural diversity.